Screening of 20 Mycobacterium tuberculosis sRNAs in plasma for detection of active pulmonary tuberculosis. (July 2021) - Han, Xue; Li, Ting; Fan, Yunfan; Wang, Xinyang; Gu, Wei; Lu, Weinan; Yin, Yian; Meng, Qingtai; Zhang, Wenli; Zhao, Jizi; Zhang, Fengmin; Fu, Yingmei
Abstract: Background: Mycobacterium tuberculosis (MTB) sRNAs are abundant. However, the level of MTB sRNA in peripheral blood remains elusive. Methods: Twenty MTB sRNAs annotated in the reference genome of H37Rv were detected in the plasma of 170 active pulmonary tuberculosis patients and 124 healthy people by qRT-PCR detection system. The differential expression of sRNAs were analyzed in two groups. The value of sRNAs for diagnosis of active tuberculosis were evaluated by ROC curve analysis. Results: Eight of the 20 sRNAs (MTS2823, MTS0997, MTS1338, ASdes, G2, C8, mcr15 and MTS1082) were found in at least 50% of the samples detected. The relative expression levels of MTS2823, MTS0997, MTS1338 and ASdes in plasma of tuberculosis patients were statistically higher than those in healthy controls. ROC curve analysis showed that the AUC of MTS0997, MTS1338, MTS2823 and ASdes were 0.8935 (95% CI 0.8109–0.9760), 0.8722 (95% CI 0.7862–0.9581), 0.8208 (95% CI 0.7246–0.9170) and 0.5792 (95% CI 0.4240–0.7344), respectively. The AUC value of combination of MTS0997, MTS1338 and MTS2823 was 0.914 (95% CI 0.8281–0.9926). Conclusions: MTB sRNAs MTS2823, MTS0997 and MTS1338 have the potential to be plasma biomarkers for active pulmonary tuberculosis. Highlights: Twenty sRNAs annotated in MTB genome have been detected in human plasma samples. Expression levels of sRNAs screened were higher in TB patients than healthy controls. Three MTB sRNAs might be considered as potential diagnosis biomarkers.